2018
DOI: 10.20892/j.issn.2095-3941.2017.0174
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA PVT1 promotes ovarian cancer progression by silencing miR-214

Abstract: Objective:Emerging evidence indicates that long non-coding RNAs (lncRNAs) are critical in carcinogenesis and progression of ovarian cancer. This study aimed to explore the functions and molecular mechanisms of plasmacytoma variant translocation I (PVT1) in ovarian cancerMethods:PVT1 and miR-214 were detected by qRT-PCR assays in ovarian cancer tissues and cells. The cell proliferation, migration, and invasion abilities were detected by cell functional experiments, respectively. Western blot assay was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(43 citation statements)
references
References 35 publications
0
42
0
Order By: Relevance
“…The reports on miRNAs-mediated tumorigenicity are comparatively more but, of late, there has been increasing interest in the lncRNAs in cancers in general 8 10 and in OC in particular 11 . Interestingly, the biological action of lncRNAs itself often involves regulation of miRNAs, including in OC 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The reports on miRNAs-mediated tumorigenicity are comparatively more but, of late, there has been increasing interest in the lncRNAs in cancers in general 8 10 and in OC in particular 11 . Interestingly, the biological action of lncRNAs itself often involves regulation of miRNAs, including in OC 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Plasmacytoma Variant Translocation 1 (PVT1) is a long non-protein-coding gene, located at chromosome 8q24 and contains approximately twelve exons and encodes a cluster of six microRNAs ( Ilboudo et al 2015 ; Colombo et al 2015 ). Several studies have reported that PVT1 plays a role in tumorigenesis, proliferation, apoptosis, cell cycle progression, migration, and invasion ( Chen et al 2018a ; Derderian et al 2019; He et al 2019 ; Pal et al 2019 ; Onagoruwa et al 2020 ). Aberrations of PVT1 are associated with different malignancies including cervical cancer, bladder cancer, colorectal cancer, gastric cancer, breast cancer, hepatocellular carcinoma, lung cancer, and breast cancer ( Wan et al 2016 ; Iden et al 2016 ; Chen et al 2018b ; Tang et al 2018 ; He et al 2019 ; Yu et al 2019 ).…”
mentioning
confidence: 99%
“…Chen and colleagues identified increased PVT1 and decreased miR-214 expression levels in EOC tissue samples and OC cell lines in comparison to normal tissue samples and human primary ovarian cells, respectively. In vitro results demonstrated the interaction between EZH2 and PVT1 and the association of the lncRNA with proliferation, migration, and invasion [86].…”
Section: Lncrnas Involved In Epigenetic Mechanisms In Ovarian Cancermentioning
confidence: 96%
“…Thus, FAL1 has an oncogenic function in OC partly exerted by the epigenetic regulation of p21 expression levels, hinting at potential implications for cancer therapy [84]. The lncRNA PVT1 recruits the protein EZH2 to the promoter of miR-214 [86]. EZH2 is one of two alternative catalytic subunits of PRC2 and is required, along with two other core components (SUZ12 polycomb repressive complex 2 subunit and embryonic ectoderm development), to produce the repressive histone modifications that characterize PRC2 activity: mono-, di-, and trimethylation of histone H3 at lysine 27.…”
Section: Lncrnas Involved In Epigenetic Mechanisms In Ovarian Cancermentioning
confidence: 99%